2021
DOI: 10.1186/s13287-020-01955-6
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue-derived stem cells in breast reconstruction: a brief review on biology and translation

Abstract: Recent developments in adipose-derived stromal/stem cell (ADSC) biology provide new hopes for tissue engineering and regeneration medicine. Due to their pluripotent activity, paracrine activity, and immunomodulatory function, ADSCs have been widely administrated and exhibited significant therapeutic effects in the treatment for autoimmune disorders, neurodegenerative diseases, and ischemic conditions both in animals and human clinical trials. Cell-assisted lipotransfer (CAL) based on ADSCs has emerged as a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 152 publications
0
19
0
Order By: Relevance
“…To date, the contribution of MSCs in BC progression has been investigated mainly by using murine MSCs (mMSCs), human bone marrow-derived MSCs (BM-MSCs) or human abdominal adipose tissue (AT)-derived MSCs. However, biological differences between BM-MSCs and AT-derived MSCs have been described and, in the context of AT, the functional diversity of depots is well established [ 16 , 17 , 36 ]. Indeed, although different studies reported that MSCs support BC cell growth and migration [ 9 , 23 ], a piece of literature assigns tumor-suppressive functions to MSCs, considering them as suitable carriers for anti-cancer drug delivery [ 22 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the contribution of MSCs in BC progression has been investigated mainly by using murine MSCs (mMSCs), human bone marrow-derived MSCs (BM-MSCs) or human abdominal adipose tissue (AT)-derived MSCs. However, biological differences between BM-MSCs and AT-derived MSCs have been described and, in the context of AT, the functional diversity of depots is well established [ 16 , 17 , 36 ]. Indeed, although different studies reported that MSCs support BC cell growth and migration [ 9 , 23 ], a piece of literature assigns tumor-suppressive functions to MSCs, considering them as suitable carriers for anti-cancer drug delivery [ 22 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, adipose tissue (AT) is an abundant source of mesenchymal stromal/stem cells (MSCs) showing self-renewal activity, multi-lineage differentiation potential and secreting a plethora of factors with immunomodulatory, angiogenic, neurotrophic, pro- and anti-inflammatory functions [ 16 , 17 , 18 ]. MSCs are largely modified by external stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-assisted lipotransfer (CAL), SVF and ASCs have demonstrated promise in adipose tissue regeneration and augmentation ( Zhu et al, 2015 ; Li et al, 2017 ; Hong, 2020 ). The administration of ASCs enhances the outcomes of fat grafting in humans, particularly breast reconstruction, facial reconstruction and cosmetic surgery applications ( Shukla et al, 2020b ; Fang et al, 2021 ). This is mainly due to the ability of ASCs to differentiate into endothelial and epithelial cells as well as secrete cytokines and growth factors that promote angiogenesis through paracrine mechanisms and cell-cell interactions in a co-culture system, thus enhancing neovascularization and accelerating wound healing ( Nie et al, 2011 ; Haubner et al, 2013 ).…”
Section: Current Therapeutic Applications Of Ascsmentioning
confidence: 99%
“…Compared with bone marrow, ASC yield from fat-tissue liposuction is 500-fold greater, with easier access, a less invasive harvesting procedure, fewer complications, and less damage to the donor sites [2]. Due to these practical advantages, ASC-based cell therapies have been widely applied for volumetric enhancement, wound healing, and soft tissue and bone regeneration [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%